PENGARUH METODE PEMBELAJARAN DAN GAYA BELAJAR TERHADAP HASIL BELAJAR IPA - Ika Yuwanita; Happy Indira Dewi; Dirgantara Wicaksono (Universitas Muhammadiyah Jakarta, 2020)
This research aims to know the influence of the method of learning and learning style against the results of the Study IPA. This research uses experimental methods with quantitative research design treatmen by level 2x2. The instruments used to study results of multiple choice tests and is used for visual learning style is the questionnaire. The results of this study indicate that: (1) student learning outcomes given Expository learning methods in higher Learning of students who are granted for Conventional learning methods Learning (2) there is the influence of the interaction between the learning methods and visual learning style (3) the results of the study and science students who have high visual learning style and learning methods given expository learning higher than students who were given conventional learning methods learning (4) the results of the study and science students who have low visual learning style and learning methods given expository learning lower than students who were given conventional learning methods learning.